PENGARUH MODAL INTELEKTUAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muhammad Azhar Arief; Erliana Erliana; Idhar Yahya (Program Magister Akuntansi Unsyiah, 2014)
ABSTRACT The purpose of this study was to find out, analyze an obtaine empirical proof about the influence of intellectual capital proxied through the Value Added Human Capital (VAHC), Value Added Employed (VACE), and Value Added Structural Capital (VASC) on the value of the companies listed in the Indonesia Stock Exchange, directly or with financial performance (ROE) as the intervening variable. The population of this study was 35 banking companies listed in the Indonesia Stock Exchange from 2009 to 2012, and 27 banking companies were selected to be the samples for this study based on the purposive sampling criteria. The data used in this study were the secondary data in the form of timeseries data with 3-yeas dimensions pooled from the 27 sample companies that the observation done were 81 observations. The data obtained wew analyzed through descriptive stastic analysis method and inferential stastic methodincluding: classical assumption test, multiple linear regression analysis, and modeling as well as determination coefficient analysis. The hypothesis in this study was proven simultaneously through F-test, partially hypothesis was tested through T-tested and path analysis. The conclution drawn from the result of data analysis showed that there was an influence of intellectual capital proxied through the Value Added Human Capital (VAHC), Value Added Capital Employed (VACE) and Value Added Structural Capital (VASC), on the value of the companies listed in the Indonesia Stock Exchange, directly or with financial performance (ROE) as the intervening variable. Keywords: Intellectual Capital, Financial Performance, Value of Company